2011
DOI: 10.4014/jmb.1105.05056
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Polymorphism in AHL-Lactonase Gene (aiiA) of Bacillus

Abstract: To explore bacterial diversity for elucidating genetic variability in acylhomoserine lactone (AHL) lactonase structure, we screened 800 bacterial strains. It revealed the presence of a quorum quenching (QQ) AHL-lactonase gene (aiiA) in 42 strains. These 42 strains were identified using rrs (16S rDNA) sequencing as Bacillus strains, predominantly B. cereus. An in silico restriction endonuclease (RE) digestion of 22 AHL lactonase gene (aiiA) sequences (from NCBI database) belonging to 9 different genera, along w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 41 publications
0
48
0
3
Order By: Relevance
“…QSIs have been primarily targeting biosynthesis and degradation of signal molecules and their receptors. QSI from prokaryotes, animal and plant origin, have been widely reported [2][3][4][5][6]. Synthetic QSIs have more variety, efficacy and efficiency in comparison to naturally occurring ones [3].…”
mentioning
confidence: 99%
“…QSIs have been primarily targeting biosynthesis and degradation of signal molecules and their receptors. QSI from prokaryotes, animal and plant origin, have been widely reported [2][3][4][5][6]. Synthetic QSIs have more variety, efficacy and efficiency in comparison to naturally occurring ones [3].…”
mentioning
confidence: 99%
“…3) AHL-based QS in some pathogenic species are well studied and have been shown to relate to their virulence [6]. It has been reported that some prokaryotes and a few eukaryotic organisms, especially Bacillus spp., can produce AHL-degrading enzymes such as AHL-lactonases and AHL-acylases to degrade these signals, which is called quorum quenching (QQ) [23,24]. QQ can be exploited as potentially novel antibiotic-free therapeutics to protect from bacterial infections [25].…”
Section: Detection Of Ahl Activity In Edw Ictaluri Ei-151mentioning
confidence: 99%
“…There are several reports which have shown the production of such type of communication molecules from bacterial organisms such as Edwardsiella ictaluri [17]. Besides to these QS molecules, production of some other molecules which can degrades these QS signals by inhibiting the production of QS signal molecules or degradation of the AHLs, also has been reported from bacterial organisms, called quorum quenching (QQ) [18][19][20][21]. Natural genetic transformation is also believed to be the essential mechanism for exploiting innate microbial capacity in bacterial populations, during mixed culture fermentation via horizontal gene transfer.…”
Section: Enhancement Of Antimicrobial Activity During Mixed Culture Fmentioning
confidence: 99%